SYSTEMIC CHANGE : FUNCTIONS OF THE CENTRAL OFFICE SUPERVISOR THAT SUPPORT INCREASED ACHIEVEMENT FOR ALL STUDENTS - Cobb, Terri Rogers (East Carolina University, 2010)
A detailed review of the history of education documented the role of the central office supervisor as being overlooked as a contributing factor to increased student achievement. The emerging research warns that improvements in student achievement will fail to reach the majority of the schools and can rarely be sustained without substantial involvement from the central office. Utilizing a synthesis of the current research, a theoretical framework and related survey instrument addressing current leadership roles and responsibilities of the central office administrator in the improvement of student achievement were developed. Principals in a large, urban district completed the 55-item survey instrument. To further explore perceptions, a focus group was conducted.   In order to determine internal consistency reliability, Cronbach's Alpha or Reliability Coefficient was computed for each of the domains on the survey. The results of Cronbach's Alpha Test for Reliability ranged from .706 to .855, which fell within the adequate to good range. The total numbers, percentages, and frequency distributions for responses on the survey instrument were calculated for each of the statements, as well as the thematic domains. In addition, Fisher's exact tests were conducted to determine if there were relationships in responses for principals in schools that made Adequate Yearly Progress (AYP) and principals in schools that did not make AYP. Fisher's exact tests examined the null hypotheses at the .05 significance level, or p < .05.   The findings of the study supported essential functions for the central office in improving student achievement. Furthermore, this study revealed that a statistical relationship did not exist between the perceptions of principals in schools that met AYP and principals of schools that did not meet AYP. The findings, implications, and recommendations for further study are discussed.
Keywords: Education, General; School management and organization; Academic achievement